(untitled) (Research, Society and Development, 2020)
Interprofessional education (IPE) is based on a strategy, that students from two or more professions learn about others and among themself, in order to provide effective collaboration and improve health outcomes. Over the years, EIP has been strengthening among countries, working in the change of the traditional model of teaching in institutions. However, it is clear that its practice in the post-graduate scope has been little discussed. Thus, this article aims to analyze the impact that interprofessional education offers for the teaching and learning of graduate students. It is an integrative review of articles published in the electronic journals, such as, Pubmed, Scielo, Lilcas, and Scopus, through which it gathered a quantity of 09 articles. Studies have shown that IPE is capable of improving interprofessional attitudes in teamwork, giving new meaning to work practices, in addition to providing a closer relationship between students and professionals, increase confidence, attitude and co-responsibility. A number of barriers been identified in the training of professionals capable of collaborative work and a large presence of traditional education in their training. It is necessary to expand the discussions involving the subject, in order to provide ways to improve future studies and interventions on the implementation of an interprofessional education in the scope of postgraduate studies.